Nekatere značilnosti dobrega vodenja šolskega tima - Logar, Vesna (Revija za elementarno izobraževanje, 2009)
Selected characteristics of good team leadership. The theoretical part describes some characteristics of good team leadership. The article then describes team management and the selection of team members, the evaluation of a team, and when a team is successful. In the empirical research work, we explore how individuals lead their teams at the schools where they teach. We were interested in whether there exists any differences between these teams based on the gender of the employees, age and seniority. The sample consisted of 65 employees at two primary schools. The data was processed at the level of descriptive statistics. For this we use the following procedures: an analysis of how well a team is maintained on the basic descriptive level, an analysis of variances and an analysis of the interaction. The rating scale was offset somewhat because less than 30 percent of the our sample were male teachers. However, our research revealed that men run teams slightly better and that the better team leaders are those who have more seniority.